2017
DOI: 10.1515/hepo-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic toxicity evaluations of aqueous extract from stem bark of Grewia mollis (Malvaceae) in rats

Abstract: SummaryIntroduction: Different parts of Grewia mollis Juss. (Malvaceae) are commonly used in folk medicine to treat several ailments, including diarrhea, ulcers, rickets, cough and fever. Although several studies have proved its therapeutic effectiveness, there are very few toxicological studies on the plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…7,8,24 In the model plant which is induced GGPS gene as a structural enzyme in the terpenoid biosynthesis pathway. 12,13,14,25 In this study, the expression of two of the seven teak GGPS, namely the GGPS3 and GGPS6 genes have an expression pattern of up and down-regulation as part of the terpenoid biosynthesis process in young and old leaves. The results of DEG and qRT PCR gene expression analysis showed that GGPS6 maintained the up-regulation trend in the regulation of terpenoid formation.…”
Section: The Ggps3 and Ggps6 Expression Profiles In Teak Leavesmentioning
confidence: 88%
“…7,8,24 In the model plant which is induced GGPS gene as a structural enzyme in the terpenoid biosynthesis pathway. 12,13,14,25 In this study, the expression of two of the seven teak GGPS, namely the GGPS3 and GGPS6 genes have an expression pattern of up and down-regulation as part of the terpenoid biosynthesis process in young and old leaves. The results of DEG and qRT PCR gene expression analysis showed that GGPS6 maintained the up-regulation trend in the regulation of terpenoid formation.…”
Section: The Ggps3 and Ggps6 Expression Profiles In Teak Leavesmentioning
confidence: 88%
“…at day 0, day 7, day 14, day 21 and day 28. Untreated rats (group one) served as the control and was administered 2 ml of distilled water (Agu, 2016;Pongri and Igbe, 2017).…”
Section: Extract Administrationmentioning
confidence: 99%
“…10 Acute and subacute oral administration of stem bark for 28 days suggests it was relatively safe in rodents. 11 The stem bark and leaves are used to treat ulcers, rheumatism, and © 2023 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License snakebites, diarrhea, obesity.…”
Section: Introductionmentioning
confidence: 99%